Anthropo-Centrism to Cosmo-Centrism: Extending Wisdom of the Bhagavad Gita to Strengthen Sustainability’s Core - Dange, Pravin; Chitrao , Pradnya; Raheja , Kumendra (Millah: Journal of Religious Studies, 2026)
This paper seeks to extend the wisdom of Bhagavad Gita to overcome the philosophical limitations of the sustainability conceptualization. The modern concept of sustainability has often been criticized for being anthropocentric and non-inclusive. Its ignorance of existing philosophical traditions further poses limitations on wider scale adoption of the concept. The concept needs to evolve beyond its current anthropocentric view, rooted in Cartesian dualism and Kantian categorical imperatives, to embrace eastern cultural perspectives rooted in non-dualism of the Vedic traditions. The traditional wisdom across cultures will strengthen its philosophical foundations and make it inclusive. The Bhagavad Gita can potentially contribute to enhance the current conceptualization of sustainability at both philosophical and operational level. Using the Gadamerian (philosophical) hermeneutics as a method, the paper demonstrates, how the wisdom in the verses of the Bhagavad Gita's can address sustainability's limitations the paper demonstrates how the wisdom in the verses of the Bhagavad Gita can address sustainability's limitations. It demonstrates, how the wisdom can help overcome the myopic, anthropocentric view of sustainability and make it more inclusive, cross-culturally relevant, and pragmatic. By integrating the diverging Western and Eastern philosophical approaches, we demonstrate how the core of sustainability can be strengthened.